2003
DOI: 10.1080/0265204031000093041
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of plasmid DNA in PLGA-stearylamine microspheres: a comparison of solvent evaporation and spray-drying methods

Abstract: Stearylamine, a positively charged hydrophobic molecule, was tested as a formulation agent for the encapsulation of a model plasmid in PLGA microspheres. The primary objective was to compare the spray-drying and double emulsion solvent evaporation methods and evaluate their suitability for fabricating PLGA-stearylamine plasmid-entrapped microspheres. A luciferase reporter gene plasmid (pGL3-Con) was formulated into microspheres using a 64 kDa PLGA 50:50 polymer blended with stearylamine (SA) at a range of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In addition, the particle sizes were not influenced by the lecithin concentration, and all the three spray-dried mannitol/lecithin powders had mean diameters of 3.7 µm, evidently smaller than the size of the pantoprazole-loaded microparticles (mean particle size of 22.0±1.2 µm). The spray-dried mannitol/ lecithin powders had mean diameters compatible to those described in the literature for powders prepared using the same type of equipment (11,39), in which a model plasmid was encapsulated in PLGA/stearylamine microparticles by spray drying (39). The microparticles became more uniform in size and less aggregated and more flowable with the increase of stearylamine.…”
Section: Characterization Of the Spray-dried Mannitol/lecithin Powdersmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, the particle sizes were not influenced by the lecithin concentration, and all the three spray-dried mannitol/lecithin powders had mean diameters of 3.7 µm, evidently smaller than the size of the pantoprazole-loaded microparticles (mean particle size of 22.0±1.2 µm). The spray-dried mannitol/ lecithin powders had mean diameters compatible to those described in the literature for powders prepared using the same type of equipment (11,39), in which a model plasmid was encapsulated in PLGA/stearylamine microparticles by spray drying (39). The microparticles became more uniform in size and less aggregated and more flowable with the increase of stearylamine.…”
Section: Characterization Of the Spray-dried Mannitol/lecithin Powdersmentioning
confidence: 55%
“…The microparticles became more uniform in size and less aggregated and more flowable with the increase of stearylamine. Particle size ranged from 2.1 to 8.3 μm, depending on the stearylamine concentration (39). In another research, DNA microparticles were prepared with polyethylenimine as a complexation agent for DNA (11).…”
Section: Characterization Of the Spray-dried Mannitol/lecithin Powdersmentioning
confidence: 99%
“…Li et al have used calcium-phosphate to precipitate plasmid DNA to form PLGA microparticles [15]. Stearylamine [16] and polyethylenimine (PEI) [17] have also been used to encapsulate plasmid DNA into PLGA microparticles. Kasturi et al have shown that plasmid DNA adsorbed on PEI-surface conjugated PLGA microparticles leads to enhanced gene delivery in macrophages [18].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, bioactivity of biopharmaceutical can be eliminated due to the presence of organic solvents, and the solvents are also difficult to remove completely (Freitas et al, 2005). Spray drying is frequently being employed to prepare microspheres (Atuah et al, 2003;Johansen et al, 2000); but, there are drawbacks to this method that makes it ineffective. These drawbacks include: it is infeasible for temperature sensitive compounds; it has considerable product lost due to inefficient separation in the collecting process (Johansen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%